2012
DOI: 10.1186/1746-6148-8-70
|View full text |Cite
|
Sign up to set email alerts
|

Is there adaptation of the exocrine pancreas in wild animal? The case of the Roe Deer

Abstract: BackgroundPhysiology of the exocrine pancreas has been well studied in domestic and in laboratory animals as well as in humans. However, it remains quite unknown in wildlife mammals. Roe deer and cattle (including calf) belong to different families but have a common ancestor. This work aimed to evaluate in the Roe deer, the adaptation to diet of the exocrine pancreatic functions and regulations related to animal evolution and domestication.ResultsForty bovine were distributed into 2 groups of animals either fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…In the study of Guilloteau et al (2012) performed on young and adult roe deer, higher proteases (chymotrypsin and elastase II) activities than in milk-fed and weaned calves were found. Differences in the pancreatic enzymes activity between those ruminants could result from their digestive system function and feeding behaviour.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the study of Guilloteau et al (2012) performed on young and adult roe deer, higher proteases (chymotrypsin and elastase II) activities than in milk-fed and weaned calves were found. Differences in the pancreatic enzymes activity between those ruminants could result from their digestive system function and feeding behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…Such proteins form complexes with tannins and comprise the first line of defence against tanninrich plants. Guilloteau et al (2012) showed that proteases activity could be closely related with PRPs secretion in saliva. In the present study insignificant changes in chymotrypsin activity after tannins supplementation were observed.…”
Section: Discussionmentioning
confidence: 99%
“…The enzymes usually measured in a pet clinic when pancreatic damage is suspected are amylase and lipase (Bellier 2010), but because this disease is difficult to diagnose, this evaluation is more complex in wild animals (Guilloteau et al 2012). Although further studies on the physiology of this gland in giant anteaters are needed, it is important to know the reference values of these enzymes, since it is helpful in the diagnosis when there is clinical suspicion of pancreatic alterations.…”
Section: Discussionmentioning
confidence: 99%